Modification of the graphene oxide surface with copper pentacyanonitrosylferrate nanoparticles for electro-oxidation of hydrazine - Maraldi, Vitor Alexandre [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (Springer Nature, 2020)
The preparation of graphene oxide and the modification of its surface directly with copper pentacyanonitrosylferrate (III) nanoparticles are presented in this work, as well as the characterization of the materials using Fourier-transform infrared spectra, X-ray diffractometry and scanning electron microscopy techniques. Beyond that, the study on the electrochemical behavior of the dispersed bimetallic complex on the graphene oxide, as known as GOCuNP, surface was carried out by the cyclic voltammetry technique. The graphite paste electrode modified with GOCuNP was successfully applied in the detection of hydrazine, presenting limit of detection of 1.58 × 10–6 mol L−1 at concentration range of 1.00 × 10–5 to 5.00 × 10–3 mol L−1 of hydrazine, being so the proposed bimetallic complex formed can be considered as a potential candidate for the manufacturing of electrochemical sensors for hydrazine detection.
Keywords: Cyclic voltammetry; Electro-oxidation; Graphene oxide; Hydrazine; Pentacyanonitrosylferrate